pegegog 2022
DOI: 10.47750/pegegog.12.01.08
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in implementing extensive reading (ER) programs: Voices from English teachers at Indonesian secondary schools

Abstract: This article reports on the implementation of extensive reading (ER) among English teachers of secondary schools and the challenges they face as a part of their efforts in supporting the Indonesian government program of school literacy initiative (SLI). The data were obtained from an online survey to a group of English language teachers (N = 22) from 22 different schools in one regency in East Java Province, Indonesia. The survey was then followed by a focused group discussion (FGD). The results show that in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…Overall, the data on personal reading resources and school reading resources indicate similar trends of responses in that only a few teachers had excellent collections, the majority had satisfactory collections, and many admitted poor collections of reading resources. Regarding school collection in particular, our findings are consistent with what has been empirically proven by Wulyani et al (2022), reporting that one of the many challenges Indonesian EFL teachers faced in implementing extensive reading activities to support the success of SLI programs at schools was the insufficiency of reading materials. The EFL teachers in their study suggested further that SLI programs would not run effectively without full support from various parties, especially from schools, in the form of the provision of reading resources (Wulyani et al, 2022).…”
Section: Reading Engagement As Reflected In the Quality Of Reading Re...supporting
confidence: 89%
See 1 more Smart Citation
“…Overall, the data on personal reading resources and school reading resources indicate similar trends of responses in that only a few teachers had excellent collections, the majority had satisfactory collections, and many admitted poor collections of reading resources. Regarding school collection in particular, our findings are consistent with what has been empirically proven by Wulyani et al (2022), reporting that one of the many challenges Indonesian EFL teachers faced in implementing extensive reading activities to support the success of SLI programs at schools was the insufficiency of reading materials. The EFL teachers in their study suggested further that SLI programs would not run effectively without full support from various parties, especially from schools, in the form of the provision of reading resources (Wulyani et al, 2022).…”
Section: Reading Engagement As Reflected In the Quality Of Reading Re...supporting
confidence: 89%
“…Regarding school collection in particular, our findings are consistent with what has been empirically proven by Wulyani et al (2022), reporting that one of the many challenges Indonesian EFL teachers faced in implementing extensive reading activities to support the success of SLI programs at schools was the insufficiency of reading materials. The EFL teachers in their study suggested further that SLI programs would not run effectively without full support from various parties, especially from schools, in the form of the provision of reading resources (Wulyani et al, 2022). Schools need to provide not only students but also teachers with an array of reading materials, with choices to access different reading media (soft or hard copy materials), in their attempts to foster school literacy culture.…”
Section: Reading Engagement As Reflected In the Quality Of Reading Re...supporting
confidence: 89%
“…Extensive reading enhances reading fluency and speed, but it also encourages learners to pay less attention to specifics (Bamford & Day, 2004). Wulyani et al (2022) state that English teachers have a good comprehension of ER as a tactic for bolstering the achievement of students learning English as a second language (SLI), but not all of them put it into practice in their classrooms. This is due to challenges such as an excessive amount of work to complete, a dearth of ready-to-implement materials and activities, and inadequate support from the government and school administration.…”
Section: B Problems Of Extensive Reading (Er)mentioning
confidence: 99%
“…Some institutions are unable to provide many references. Teachers expressed that their schools lack English references [8], preventing them from implementing extensive reading. It is one of the challenges in implementing extensive reading at certain schools or universities in Indonesia.…”
Section: Introductionmentioning
confidence: 99%